2007
DOI: 10.1200/jco.2007.13.2142
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Cancer Diagnosis: Current Understanding and Future Directions

Abstract: Purpose Errors in cancer diagnosis are likely the most harmful and expensive types of diagnostic errors. We reviewed the literature to understand the prevalence, origins, and prevention of errors in cancer diagnosis, focusing on common cancers for which early diagnosis offers clear benefit (melanoma and cancers of the breast, colon, and lung). Methods We searched the Cochrane Library and PubMed from 1966 until April 2007 for publications that met our review criteria and manually searched references of key publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 141 publications
2
74
0
1
Order By: Relevance
“…In melanoma, prognostic markers are needed that would help to refine the risk of progression, assess the clinical outcome and select optimal treatment strategies (1)(2)(3). In normal epithelial cells, transforming growth factor-ß (TGF-ß) acts as a strong inhibitor of cell growth (4).…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma, prognostic markers are needed that would help to refine the risk of progression, assess the clinical outcome and select optimal treatment strategies (1)(2)(3). In normal epithelial cells, transforming growth factor-ß (TGF-ß) acts as a strong inhibitor of cell growth (4).…”
Section: Introductionmentioning
confidence: 99%
“…For a reader to distinguish a lesion in a background of anatomical noise, the lesion needs to be an order of magnitude larger than the same lesion on a quantum-limited background [3]. Another report determined that anatomical obstructions result in a 71 % miss rate [18]. Viewing biplane images stereoscopically provides the radiologist with a visual reduction of anatomical noise.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the current study demonstrated no histopathological confirmations but substantial interobserver variability in GTV contouring. Although previous studies suggested that the "double reading" can reduce errors in diagnostic radiology [10,11] , efforts are underway in our institution to resolve these issues, especially the accuracy of GTV assessments in the "double reading" system. Nevertheless, the "double reading" system should provide the clinical consensus and the clinical training in GTV contouring.…”
Section: Discussionmentioning
confidence: 99%
“…Errors in diagnostic radiology are common, and dialogue among clinicians and radiologists, the evaluation of multimodal images, and iterative readings are thought to decrease the error [10][11][12][13][14] . Therefore, a practical consensus for GTV assessments, similar to the "double reading" approach, must be developed.…”
Section: Introductionmentioning
confidence: 99%